2018
DOI: 10.18203/2349-3291.ijcp20181981
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of hypoxemia in children with WHO classified pneumonia

Abstract: Background: In developing countries were health providers have to rely on signs and symptoms to identify hypoxemia in pneumonia and start oxygen therapy, this study was therefore conducted to assess the prevalence and predictors of hypoxemia with the hypothesis to design a severity score for hypoxemia in children with pneumonia.Methods: This prospective observational study was carried out at the paediatric emergency department of Gajra Raja Medical College, Gwalior, on children of age 1-60 months admitted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…The prevalence of hypoxemia in this study was higher than other studies conducted in Ethiopia (57.0%) [ 17 ], Colombia (47%) [ 19 ], Nepal (38.5%) [ 20 ], another study in Nepal (51%) [ 21 ], India (33.5%) [ 22 ] Peru (10%) [ 13 ], and the Netherlands (45%) [ 14 ]. This discrepancy might be due to variations in the health care system, variations in access to adequate healthcare services, health care facilities, and variations in the habit of proper hygiene and sanitation, which leads to respiratory tract infection, unclean water, inadequate access to food, which leads to immune suppression, and low levels of immunization coverage.…”
Section: Discussioncontrasting
confidence: 73%
“…The prevalence of hypoxemia in this study was higher than other studies conducted in Ethiopia (57.0%) [ 17 ], Colombia (47%) [ 19 ], Nepal (38.5%) [ 20 ], another study in Nepal (51%) [ 21 ], India (33.5%) [ 22 ] Peru (10%) [ 13 ], and the Netherlands (45%) [ 14 ]. This discrepancy might be due to variations in the health care system, variations in access to adequate healthcare services, health care facilities, and variations in the habit of proper hygiene and sanitation, which leads to respiratory tract infection, unclean water, inadequate access to food, which leads to immune suppression, and low levels of immunization coverage.…”
Section: Discussioncontrasting
confidence: 73%
“…These findings are consistent with previous studies conducted on predictors of hypoxemia. 18,19,20,21,22 Final prediction model in this study showed difficulty in breathing as a final predictor of hypoxemia.…”
Section: Discussionmentioning
confidence: 65%
“…17 of hypoxemia in children with pneumonia may be due to differences in characteristics of study populations, severity of pneumonia, cut-off values and definitions of hypoxemia, methods of measurement of hypoxemia, presence of comorbid conditions, and geographic region and altitude of study setting. 16,18 Numerous studies have recognized the need to identify predictors of hypoxemia in resourcelimited settings, each with varying results. This present study identified difficulty breathing, tachypnea, and subcostal retractions as significantly more likely to be observed in those with hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in oxygen pressure in the blood, a condition called hypoxemia, is often a result of pneumonia but may also result from other conditions such as asthma (Sarkar et al, 2017). Studies have shown that doctors in developing countries have found the inability to eat, cyanosis, grunting, and impaired consciousness to be among the most accurate clinical predictors of hypoxemia caused by pneumonia (Kushwah & Gaur, 2018). Although pneumonia is the most common cause of death in children, its symptoms and signs easily overlap with other respiratory and non-respiratory diseases such as malaria, making it difficult to diagnose (Scott et al, 2012).…”
Section: Analysis and Discussionmentioning
confidence: 99%